2013
DOI: 10.1590/s0100-29452013000100022
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação agronômica de parentais e híbridos de maracujazeiro- amarelo

Abstract: O presente trabalho objetiva determinar o potencial agronômico de genótipos de maracujazeiro-amarelo, visando a identificar e selecionar híbridos promissores. O experimento foi conduzido em área de produção no município de Cruz das Almas (BA), em delineamento de blocos casualizados, com três repetições, 41 genótipos (30 híbridos e 11 parentais), com parcela de 4 plantas. As características avaliadas foram: produtividade; número de frutos; massa média de frutos; espessura de casca; rendimento de suco; produtivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
4
14
0
3
Order By: Relevance
“…The production and fruit quality results presented are similar to previous studies evaluating the agronomic performance of these hybrids and other yellow passion fruit trees, with variations also resulting from the edaphoclimatic and cultivation conditions in the different regions of the country (AGUIAR et al, 2015;COSTA et al, 2009;FORTALEZA et al, 2005;FREITAS et al, 2011;GRECO et al, 2014;MARTINS et al, 2003;MELETTI, 2000;MELO et al, 2001;NEGREIROS et al, 2008;ZACCHEO et al, 2012;NEVES et al, 2013;VALE et al, 2013). Similar results are also reported for production and fruit quality of sweet passion fruit selections in other studies (ALVES et al, 2012;MELETTI et al, 2003).…”
Section: Resultssupporting
confidence: 85%
“…The production and fruit quality results presented are similar to previous studies evaluating the agronomic performance of these hybrids and other yellow passion fruit trees, with variations also resulting from the edaphoclimatic and cultivation conditions in the different regions of the country (AGUIAR et al, 2015;COSTA et al, 2009;FORTALEZA et al, 2005;FREITAS et al, 2011;GRECO et al, 2014;MARTINS et al, 2003;MELETTI, 2000;MELO et al, 2001;NEGREIROS et al, 2008;ZACCHEO et al, 2012;NEVES et al, 2013;VALE et al, 2013). Similar results are also reported for production and fruit quality of sweet passion fruit selections in other studies (ALVES et al, 2012;MELETTI et al, 2003).…”
Section: Resultssupporting
confidence: 85%
“…Fruit size is a characteristic much appreciated by consumers at the time of purchase of the yellow passion fruit (Negreiros et al, 2008), who generally prefer larger fruit weighing more than 170 g (Cavichioli et al, 2008) and with attractive appearance when intended for the fresh market. For producers, these fruits have higher classification and better prices (Neves et al, 2013). Taking this as a criterion, half of the evaluated hybrids showed fruit weight within the marketing standards, even with values well above the means found in the literature for conventional cultivation of passion fruit (Negreiros et al, 2008;Flores et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
“…Neves et al (2013), evaluating the productivity of 30 hybrids and 11 parental passion fruit trees, found mean values of 24.03 to 43.75 t ha -1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dther authors have also reported a reduction in the soluble solids content in passion fruit pulp subjected to cold storage (Goldenberg et al, 2012;Matta et al, 2006). A high SS value is an important trait for the food processing industry, since about 11 Kg of fruit with SS between 11 and 12% is necessary to obtain 1 Kg of concentrated juice at 50 °Brix (Neves et al, 2013). The higher the SS level is, the lower the quantity of fruit necessary to make concentrated juice (Nascimento et al, 2003).…”
Section: Resultsmentioning
confidence: 99%